The Routledge companion to the Christian church - Mannion, Gerard (Routledge companions, 2010)
'I am glad to commend the 'Routledge Companion to the Christian Church'. It is good that students will get a deeper knowledge of the meaning of ecclesiology and of its crucial importance for mutual understanding and ecumenical dialogue.' - Cormac Murphy O'Connor, Archbishop Emeritus of Westminster 'it is a valuable compendium of information and should be an important part of a good reference collection.' - Choice 'Good companions add value to any journey. They help us to spot landmarks on the way, explain a few things, and indicate possible ways ahead. Those who journey with the Christian Church through time and space benefit from just such good companions, and Gerard Mannion and Lewis Mudge are to be congratu-lated on their oversight of this significant project in ecclesial studies.'